2011
DOI: 10.1017/s0007114511003710
|View full text |Cite
|
Sign up to set email alerts
|

Folate malabsorption is associated with down-regulation of folate transporter expression and function at colon basolateral membrane in rats

Abstract: Folates, an essential component (important B vitamin) in the human diet, are involved in many metabolic pathways, mainly in carbon transfer reactions such as purine and pyrimidine biosynthesis and amino acid interconversions. Deficiency of this micronutrient leads to the disruption of folate-dependent metabolic pathways that lead to the development of clinical abnormalities ranging from anaemia to growth retardation. Folate deficiency due to alcohol ingestion is quite common, primarily due to malabsorption. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…However, looking at our results of experiments carried out on rats, this seems to be unlikely. Previous studies conducted on rats in various tissues have also shown decrease in folate transport on chronic alcoholism . Similar results have also been observed in case of thiamine and biotin transporters .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, looking at our results of experiments carried out on rats, this seems to be unlikely. Previous studies conducted on rats in various tissues have also shown decrease in folate transport on chronic alcoholism . Similar results have also been observed in case of thiamine and biotin transporters .…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies conducted on rats in various tissues have also shown decrease in folate transport on chronic alcoholism [9,10,17,18,31]. Similar results have also been observed in case of thiamine and biotin transporters [46,49].…”
Section: Discussionsupporting
confidence: 81%
“…Consumption of high amount of alcohol can lead to mal-absorption of folate [10,11] across intestine and thus creating FD in the body [12,13]. Various in vitro and in vivo models of alcoholism have suggested that alcoholism results in alteration of folate transport and expression of folate transporters in organs like intestine, colon, kidney, liver, and pancreas too [14][15][16][17][18]. Besides alcoholism, dietary folate alterations also have been found to affect folate uptake in intestine and kidney [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in folate transport in these tissues was due to downregulation in the expression of folate transporters [11][12][13][14]. The reduction in folate transport in these tissues was due to downregulation in the expression of folate transporters [11][12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies conducted in our lab have shown alteration in folate transport across absorptive surfaces of intestine, liver, pancreas, colon, and kidney in alcoholism. The reduction in folate transport in these tissues was due to downregulation in the expression of folate transporters [11][12][13][14]. On the other side, dietary folate deficiency in rats as well as in cell line is known to upregulate the transport as well as expression of folate transporters [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%